Highly dispersed silver imbedded into TiN submicrospheres for electrochemical detecting of hydrogen peroxide - Youqun Chu (Nature Portfolio, 2020)
Abstract We report the fabrication of silver nanoparticles evenly imbedded into TiN submicrospheres via one-pot solvothermal reaction and subsequent nitridation for electrochemical detecting of hydrogen peroxide. The precursor of TiO2 submicrospheres and high dispersion of silver nanoparticles are regulated by the alcoholysis of tetrabutyl titanate and reducibility of enol in vitamin C. The ion nitriding promoted the conductivity and micro-nano porous structure on the surface of TiN submicrospheres, which increase the dispersity of silver nanoparticles and make contributions to avoid aggregations. More importantly, the electrochemical response of Ag-TiN submicrospheres to H2O2 was remarkably enhanced due to the co-effects of Ag and N-doping. It provides a superior sensing performance for electrochemical detection of hydrogen peroxide at − 0.3 V with a high sensitivity of 33.25 μA mmol L−1 cm−2, wide linear range of 0.05–2100 μM and low detection limit of 7.7 nM. The fabricated sensor also reliably applied in detection of H2O2 in milk samples with good reproducibility, repeatability and storage stability.